(untitled) (Philological Studies, 2019)
Social and social value orientations related to management, self-awareness and life style are among the most important social orientations in any cultural environ- ment. In the research Social and social value orientations related to management, self–perception and life style by chosen groups of Slovene and non–Slovene participants, I was interested if the mentioned social interpretations differ considerably among groups of Slovenian and non-Slovenian participants or cultures of the survey. Respondents have been consisted of six different groups of students (economy stu- dents, mechanical engineering students, management students, law students, sociology students and psychology students), which have been included in the survey. A total of 269 students have been questioned, of which 246 have been Slovenians and 23 non-Slovenians. In the questionnaire I compiled together with my colleagues, I applied the Rokeach Value Scale, Hofstede’s Management Scale, Lerner’s question- naire on the justness of the world and scales related to evaluations of management and management experience. Results have shown that responses from Slovenian and non-Slovenian respondents do not differ considerably in any summation dependable variable, while they differ considerably in the value preferences World of beauty and aesthetics, Equality of all people, Family security, Politeness and Intellectuality.